Assessment of symptoms of urinary incontinence in women with polycystic ovary syndrome - Montezuma, Thais (Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, 2011)
OBJECTIVES: The pelvic floor muscles are sensitive to androgens, and due to hyperandrogenism, women with polycystic ovary syndrome can have increased mass in these muscles compared to controls. The aim of this study is to compare reports of urine leakage and quality of life between women with and without polycystic ovary syndrome. METHODS: One hundred thirteen 18- to 40-year-old nulliparous women with polycystic ovary syndrome or without the disease (controls) were recruited at the University Hospital of School Medicine of São Paulo University at Ribeirão Preto City, Brazil. The subjects were not taking any hormonal medication, had not undergone previous pelvic surgery and did not exercise their pelvic floor muscles. The women were divided into the following four groups: I- polycystic ovary syndrome with normal body mass index (n = 18), II- polycystic ovary syndrome with body mass index ≥25 (n = 32), III- controls with normal body mass index (n = 29), and IV- controls with Body Mass Index ≥25 (n = 34). Quality of life was evaluated using the SF-36 questionnaire, and the subjects with urinary complaints also completed the International Consultation on Incontinence Questionnaire Short Form to evaluate the severity of their urinary incontinence. RESULTS: The replies to the International Consultation on Incontinence Questionnaire Short Form revealed a significant difference in urinary function between groups, with 24% of the subjects in group IV reporting urinary incontinence. The mean scores for the SF-36 questionnaire revealed that group II had the lowest quality of life. CONCLUSIONS: The control obese group (IV) reported a higher prevalence of urinary incontinence. There was no difference in the reported frequency of urine loss between the polycystic ovary syndrome and control groups with normal body mass index or between the polycystic ovary syndrome and control groups with body mass index ≥25.